Correlation of mandibular radiomorphometric indices with serum calcium and serum estradiol in pre- and post-menopausal women - Lina Govind Chandak; Vidya Krushnarao Lohe; Rahul R Bhowate; Krushna P Gandhi; Neha V Vyas (Wolters Kluwer Medknow Publications, 2017)
Background: Osteoporosis is a disease that is seen commonly with increasing age. The purpose of this study was to compare the bone quality of pre- and post-menopausal women using the quantitative indices determined by measurements on panoramic radiographs (mental index, inferior and superior panoramic mandibular indices, antegonion index [AGI], and gonion index) and to determine the effects of serum calcium and serum estradiol levels on alveolar bone loss. Materials and Methods: Sixty female patients in the age group of 25-55 years were included in the study. The patients were divided into three equal groups, i.e., control Group A (twenty - premenopausal women), study Group B (twenty - postmenopausal women with healthy periodontium), study Group C (twenty - postmenopausal women with periodontitis). Quantitative indices were measured on digital panoramic radiographs of the patients and serum calcium and estradiol levels were determined. Results: Correlation of serum calcium with radiomorphometric indices of all the groups showed statistically nonsignificant differences. On correlating mean estradiol levels with radiographic indices of patients of Group A and Group B showed statistically nonsignificant differences. On correlating mean estradiol levels with radiographic indices of patients of Group C patients showed statistically significant difference with positive correlation with cortical width (P = 0.04) and AGI (P = 0.02) while statistically nonsignificant correlation with other indices. The statistical tests used for the analysis of the result were one-way ANOVA, multiple comparison Tukey test, Chi-square test, Student's t-test. Conclusion: There is a little evidence of correlation of these indices with serum estradiol and calcium levels, and therefore, detailed further research about this correlation is required.